Acute coronary syndrome secondary to cardiac infiltration and coronary occlusion of chronic lymphocytic leukemia – A case report. Issue 6 (June 2021) - Bennett, Sadie; Ravindran, Roshini; Duckett, Simon; Cubukcu, Arzu; Jones, Hefin; Kwok, Chun Shing
Abstract: A 72-year-old male with a history of chronic lymphocytic leukemia (CLL) was admitted to hospital with a productive cough and an episode of diarrhea and vomiting. He was initially treated for pneumonitis and sepsis. On the 12th day of his admission, he reported chest pain. Changes on his electrocardiogram were suggestive of myocardial ischemia and an elevated troponin rise was detected from his blood tests. A diagnosis of acute coronary syndrome was made but due to his frailty, he was medically managed. His echocardiogram revealed an external echogenic mass which invaded the anterolateral left ventricular wall. Further imaging with cardiac magnetic resonance imaging (MRI) and computed tomography (CT) thorax demonstrated external encasement of left circumflex coronary artery with mediastinal mass, leading into downstream myocardial ischemia and subsequent necrosis. He was considered suitable for aggressive radiotherapy/chemotherapy but passed away 7 days later. This case highlights the unusual case where an acute myocardial infarction can be attributed to direct infiltration and external compression of coronary artery by mediastinal tumor and the value of multi-modality imaging (echocardiogram, CT, and MRI) in identifying the cause of myocardial ischemia in patients with CLL in the end stages of the disease. <Learning objective: It is unusual that acute coronary syndrome is caused by direct tumor infiltration and obstruction of a major epicardial vessel. This case highlights the interesting and unusual scenario where tumor growth results in complete occlusion of the obtuse marginal coronary artery in a patient with chronic lymphocytic leukemia. By using multi-modal imaging, we were able to characterize the lesion and the coronary involvement.>